The Dilemma Economic Growth And Poverty Rate In Sulawesi - Kalzum R Jumiyanti; Moh. Jamal Moodoeto; Deby Rita Karundeng (MediaTrend, 2021)
Economic growth is often cited as a significantly contributive factor reduction of the poverty rate. This study aims to investigate the economic growth and poverty among all areas within Sulawesi Island and to compare these two aspects among the island’s provinces. This study employs both comparative quantitative analysis to explore economic growth formulatively and qualitative manner for in depth analysis. The result reveals an escalation in both gross regional domestic product (henceforth regional GDP) and total population each year for the last ten years. However this situation is unable to boost the macro-economic growth; a reason for this condition is the population growth in the recent ten years possibly dominated by High birth rates. Yet, this condition does not lead to a drop in the demand for workforces, which implies that the number of the working-age population (which can help improve the regional per capita income) remains constant despite the population growth. Another possible factor of regional GDP escalation is the fact that the government policy, in its foreign cooperation implementation, does not contribute to the local workforces. Nevertheless, the rise in regional GDP is insignificant as it does not affect the local economic conditions. Hence, it proves that the fluctuation of economic growth does not affect the poverty rate.